Pelanggaran Peran Sosial dan Etika Guru: Analisis Kekerasan Seksual di MAN 1 Gorontalo Berdasarkan Teori Talcott Parsons - Siti Khalimah (Fakultas Hukum, Universitas Warmadewa, 2025)
This research analyzes the case of sexual violence that occurred at MAN 1 Gorontalo through the approach of Talcott Parsons' social role theory. This case reflects a violation of the social role and professional ethics of teachers, where the teacher, as an authority figure, abuses their power over students. The spread of the pornographic video related to the incident worsened the psychological impact on the victims and damaged the school's reputation. Using a qualitative method based on literature review, this research found that the weak implementation of professional ethics and the imbalance of power relations are key factors in the occurrence of sexual violence in education. This research provides recommendations to strengthen the supervision and implementation of the teacher's code of ethics in order to create a safe and violence-free educational environment.